ASSESSMENT OF RISK FACTORS FOR THE DEVELOPMENT OF BRONCHO-OBSTRUCTIVE SYNDROME IN CHILDREN - L.A. Mukhamadieva; Ogabek Khaydarov (Ta’lim innovatsiyasi va integratsiyasi, 2026)
ABSTRACT Background: Broncho-obstructive syndrome (BOS) is a common complication of acute lower respiratory diseases in children and is associated with an increased risk of bronchial asthma. Objective: To identify and systematize risk factors contributing to the development of BOS in children with acute obstructive bronchitis (AOB). Methods: A retrospective cohort study included 912 children aged 2 months to 5 years hospitalized from 2012 to 2015. Group 1 consisted of 494 children with BOS on the background of AOB, while Group 2 included 418 children with acute bronchitis without obstruction. Statistical analysis was performed using Pearson’s chi-square (χ²) test. Results: Among 49 identified factors, 28 were statistically significant. Major risk factors included male gender, older age, allergic predisposition, atopic dermatitis, thymomegaly, passive smoking, early artificial feeding, and seasonal factors (winter and spring). Predisposing factors included frequent respiratory infections, rickets, prematurity, adverse environmental conditions, and delayed medical care. Conclusion: BOS development in children is multifactorial. Identification of modifiable risk factors enables early prevention and reduces the likelihood of progression to bronchial asthma.